Diagnostic value of maximum signal intensity on T1-weighted MRI images for differentiating parotid gland tumours along with pathological correlation. Issue 6 (June 2021) - Wei, P.Y.; Shao, C.; Huan, T.; Wang, H.B.; Ding, Z.X.; Han, Z.J.
Abstract : AIM: To investigate the efficacy of the maximum signal intensity of tumour on T1-weighted magnetic resonance imaging (MRI) images for differentiating Warthin's tumours (WTs) from pleomorphic adenomas (PAs) and malignant tumours (MTs). MATERIALS AND METHODS: One hundred and fifty-four histopathologically confirmed parotid tumours, including 76 PAs, 45 WTs, and 33 MTs, were analysed. MRI results were compared with pathological findings. The maximum signal intensity of tumour and the average signal intensity of spinal cord were measured on T1-weighted images, then the tumour-to-spinal cord signal intensity ratio (T1-max-SIR) was calculated. The distribution of T1-max-SIRs among the three groups of tumours was analysed using the Mann–Whitney U -test. Receiver operating characteristic curves were generated to assess the ability of T1-max-SIRs to differentiate parotid tumours. In addition, the interobserver agreement between readers was assessed using interclass correlation coefficient (ICC). RESULTS: T1-max-SIRs were higher in WTs than in PAs ( p< 0.001) and MTs ( p< 0.001), and no significant difference was found between PAs and MTs ( p= 0.151). The area under the curve (AUC) of T1-max-SIRs for differentiating WTs from PAs was 0.901, with a sensitivity of 91.1% and a specificity of 82.9%. The AUC of T1-max-SIRs for differentiating WTs from MTs was 0.851, with a sensitivity of 88.9% and a specificity of 78.8%. Readers had excellent interobserver agreement on T1-max-SIRs (ICC = 0.989; 95% confidence interval, 0.985–0.992). CONCLUSIONS: T1-max-SIRs can be useful for differentiating WTs from PAs and MTs with high diagnostic efficiency. Highlights: T1-max-SIR can quantify the focal high signal intensity in tumour. T1-max-SIR identifies Warthin's tumour from pleomorphic adenoma and malignant tumour. T1-max-SIR cannot distinguish pleomorphic adenoma from malignant tumour. The focal high signal intensity in tumour is related to the pathological findings.